Comparative studies of fibres of woody species selected in relation to their paper-making potentials - Ajuziogu, Godswill C.; Ojua, Eugene O.; Abu, Ngozi E.; Onyeke, Christopher C.; Ayogu, Virginius O.; Nweze, Anthony E.; Nworie, Solomon (Instituto de Ecología, A.C., 2020)
The wood fibre used by the paper industry originates primarily from forests. Apart from Gmelina arborea, there are other fast-growing plant species whose fibre characteristics are yet unknown. In order to relieve the pressure and demand on G. arborea, this work was aimed at characterizing and comparing the fibres of four tree species (Parkia biglobosa, Arzadirachta indica, Alstonia boonei and Cassia siamea) to G. arborea, with the intention of elucidating their suitability for the pulp and paper industry. The trunk wood samples used in this study were collected from the Botanical Garden of the University of Nigeria, Nsukka, while the study was conducted in the Plant Anatomy Laboratory in the Department of Plant Science and Biotechnology, University of Nigeria, Nsukka, Enugu State-Nigeria. The results showed that the mean fibre length ranged from 1.00 mm in P. biglobosa to 1.70 mm in A. boonei. The fibre lengths of G. arborea and A. booneidid do not vary significantly (P < 0.05). The Runkel ratio ranged from 0.624 to 3.227 across the species with G. arborea and A. boonei recording the lowest values. Conclusively, A. boonei is another pulp wood with good paper-making potential that could substitute the already known G. arborea.